Analisis Rasio Neutrofil Limfosit pada Pasien Carcinoma Mammae dengan Risiko Kejadian Efusi Pleura - Lolongan, Gerald Randy; Tangkilisan, Adrian; Sukanto, Wega; Langi, Fima Lanra Fredrik G. (Syifa'Medika, 2025)
Breast cancer is one of the most common cancers, with complications such as pleural effusion potentially worsening patient prognosis. This study aims to analyze the relationship between the neutrophil-lymphocyte ratio (NLR) and pleural effusion occurrence in breast cancer patients at RSUP Prof Dr. R.D. Kandou Manado. The study used a cross-sectional retrospective design, involving 196 breast cancer patients divided into two groups: those with and without pleural effusion. The results showed that while there is a tendency for higher NLR in patients with pleural effusion, other factors like cancer stage and supraclavicular lymph node enlargement play a more dominant role in predicting pleural effusion. NLR was not found to be a strong biomarker for independently predicting pleural effusion. This study provides insights into the potential of NLR for predicting complications in breast cancer patients, but further research is needed to identify more sensitive biomarkers for pleural effusion prediction.